RESEARCH RESULTS ON THE SELECTION OF THE MESH SURFACE OF A LINT-CLEANING DEVICE - Abdurahmonov, Jahongir (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
In this article, research was conducted to improve the “Linter” machine, which removes short fibers remaining in ginned cotton seeds at cotton ginneries By technical regulation, after the cotton raw material is ginned at cotton gins, the cotton seeds are lintered in Series 5LP linters to obtain lint widely used in the textile, chemical, and pulp and paper industries. However, the current state of cotton linters does not meet the growing demands of the cotton ginning industry The need to increase the productivity of the machines, improve the quality of the produced products, save energy resources and material costs in the production of lint and seeds, improve the equipment and technologies for the linting of seeds and the cleaning of lint, the optimal parameters of the working members of new machines and their operating modes. requires conducting theoretical and experimental studies that will allow us to choose.